2017
DOI: 10.1186/s12877-017-0630-1
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle factors are significantly associated with the locomotive syndrome: a cross-sectional study

Abstract: BackgroundThe Japanese Orthopedic Association first proposed the concept of “locomotive syndrome” in 2007. It refers to circumstances in which elderly people need nursing care services or are at high risk of requiring such services within a short time. Recently, the public health burden of providing nursing care for elderly individuals has increased. Therefore, locomotive syndrome, and the means of preventing it, are a major public health focus in Japan. The purpose of this study was to investigate the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
19
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 36 publications
5
19
1
1
Order By: Relevance
“…34.6%, high: 36.8%) than were men aged < 65 years (low: 13.6%, moderate: 13.8%, high: 17.5%); these estimates are consistent with those previously reported [26]. Concurrently, this study suggests that engagement in high-intensity sports during university does not reduce the risk of LS in middle-aged men compared to engagement in low-intensity sports.…”
Section: Discussionsupporting
confidence: 91%
“…34.6%, high: 36.8%) than were men aged < 65 years (low: 13.6%, moderate: 13.8%, high: 17.5%); these estimates are consistent with those previously reported [26]. Concurrently, this study suggests that engagement in high-intensity sports during university does not reduce the risk of LS in middle-aged men compared to engagement in low-intensity sports.…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, moderate alcohol consumption has been shown to have a protective effect against osteoporosis, while heavy alcohol intake is conversely associated with an increased risk of osteoporosis . Akahane et al reported that alcohol consumption a few times/month or a few times/week was inversely related to the presence of LS in a cross‐sectional study using an Internet panel survey. The current results indicated a similar tendency.…”
Section: Discussionmentioning
confidence: 99%
“…Seven questions were prepared for participants in the Loco-check questionnaire by the Japanese Orthopaedic Association (JOA) to evaluate locomotive organs. This questionnaire is simple and easy to understand even for elderly people [21], detailed contents for investigation consisted of the following questions: "1. You can't put on your sock standing on one leg", "2.…”
Section: Locomotive Syndrome Risk Testmentioning
confidence: 99%